2014
DOI: 10.1177/1087054714554617
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Patient Characteristics, and Pharmacological Treatment of Children, Adolescents, and Adults Diagnosed With ADHD in Sweden

Abstract: From 2006 to 2011, the number of patients diagnosed with ADHD has increased in Sweden over all ages. The majority of patients diagnosed with ADHD in Sweden received a pharmacological treatment regardless of age. An ADHD diagnosis was often accompanied with psychiatric comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
85
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 32 publications
16
85
1
2
Order By: Relevance
“…Parental report of ADHD medication usage has not been validated against a clinical standard, although one previous study has validated dispensed ADHD medications with physician diagnosis. 42 Additionally, the prevalence of adult ADHD of 4Á2% determined by the present study is comparable with the prevalence of 4Á4% found by a previous study, which was determined by clinician assessment. 43 Nevertheless, ADHD is primarily a disease of childhood onset and thus may be affected by misclassification and recall bias, particularly in the adult sample.…”
Section: Discussionsupporting
confidence: 89%
“…Parental report of ADHD medication usage has not been validated against a clinical standard, although one previous study has validated dispensed ADHD medications with physician diagnosis. 42 Additionally, the prevalence of adult ADHD of 4Á2% determined by the present study is comparable with the prevalence of 4Á4% found by a previous study, which was determined by clinician assessment. 43 Nevertheless, ADHD is primarily a disease of childhood onset and thus may be affected by misclassification and recall bias, particularly in the adult sample.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, underestimation of ADHD is probably a limitation of our study. As mentioned before, more than 80% of Swedish children and teenagers diagnosed with ADHD had reportedly used medication at some point . There is also a risk of misclassification if the studied medications were prescribed for some other condition (e.g., psychostimulants for rare disorders such as narcolepsy).…”
Section: Discussionmentioning
confidence: 99%
“…As in many Western countries, [12][13][14][15][16][17][18][19][20][21] the medication of ADHD in Israel has risen substantially over the past decade and a half. 22 The overall prescription of stimulants used to treat ADHD and covered by the national healthcare system doubled in 2005-2012, from 4.0 to 9.9 defined daily doses per 1000 inhabitants per day.…”
Section: Introductionmentioning
confidence: 99%